An in vivo comparison of internal bacterial colonization in two dental implant systems: Identification of a pathogenic reservoir. (April 2014) - Mawhinney, Joanne; Connolly, Eimear; Claffey, Noel; Moran, Gary; Polyzois, Ioannis
Abstract Objectives. The aim of this study was to compare internal bacterial colonization in two implant systems, one screw root form (SRF) with an external hexagon connection and one plateau root form (PRF) with a Morse taper internal connection. Materials and methods. Thirty-two implants; 12 SRF and 20 PRF, were sampled in 15 patients. All implants had been in function for at least 6 months prior to sampling. The implant restoration was removed and 10 µl of sterile saline was introduced into the implant well via a sterile glass syringe. The saline was drawn back up and transferred to the laboratory for microbiological analysis. The number of aerobic and anaerobic colony forming units per millilitre was determined and the dominant micro-organism in each sample was identified by 16s rRNA gene amplicon sequencing. Results. There was a significant difference between bleeding on probing around the SRF implants (3%) and the PRF implants (28%) (p = 0.0496). Bacterial colonization was identified at 11 SRF and 19 PRF implants. The numbers of anaerobic bacteria recovered from PRF implants was significantly higher than that from SRF implants (p = 0.0002). Streptococcus species and Enterococcus faecalis were found to dominate. Conclusions. This in vivo study demonstrated bacterial colonization in both types of implant systems, irrespective of the type of connection. Significantly greater anaerobic counts were found in the Morse taper internal connection implants.